1984
DOI: 10.1007/978-3-642-82163-9_88
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Defects on the Splitting of the Acceptor Ground State in Silicon

Abstract: The distribution of strain fields from specified defects in otherwise pure silicon crystals is reflected in the resulting distribution of splittings E of the partially orbitally degenerate rs ground state of effective mass acceptors. The spectral density N(E) can be probed by resonant scattering of h\l " E ultrasonic r IJ or 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…A subsequent PL study confirmed that the doublet splittings arose from the A 0 final state of the A 0 X PL transitions and revealed a similar 0:10 AE 0:01 cm À1 doublet splitting for the Ga A 0 ground state, and a 0:15 AE 0:03 cm À1 A 0 splitting for the deeper In acceptor [37][38][39]. The 0:15 AE 0:03 cm À1 splitting found for the indium A 0 state in the PL study [37] agrees well with the phonon spectroscopy [31] result of 0:11 to 0:16 cm À1 , and the failure to detect the B splitting ($0:043 cm À1 as determined by phonon spectroscopy [28,29,31]) in the PL studies was consistent with the PL observed linewidth of the boron BE components of $0:08 cm À1 resulting from a combination of insufficient instrumental resolution and PL broadening effects.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…A subsequent PL study confirmed that the doublet splittings arose from the A 0 final state of the A 0 X PL transitions and revealed a similar 0:10 AE 0:01 cm À1 doublet splitting for the Ga A 0 ground state, and a 0:15 AE 0:03 cm À1 A 0 splitting for the deeper In acceptor [37][38][39]. The 0:15 AE 0:03 cm À1 splitting found for the indium A 0 state in the PL study [37] agrees well with the phonon spectroscopy [31] result of 0:11 to 0:16 cm À1 , and the failure to detect the B splitting ($0:043 cm À1 as determined by phonon spectroscopy [28,29,31]) in the PL studies was consistent with the PL observed linewidth of the boron BE components of $0:08 cm À1 resulting from a combination of insufficient instrumental resolution and PL broadening effects.…”
Section: Resultssupporting
confidence: 83%
“…The acceptor states and acceptor BE transitions have been studied by a variety of different experimental techniques such as electron spin resonance (ESR) [23,24], thermal conductivity studies [32][33][34], phonon absorption spectroscopy [25][26][27][28][29][30][31]46] and, most recently, by photoluminescence [35][36][37][38][39]. While electron paramagnetic resonance (EPR) was detected for electrons bound to neutral donor impurities (D 0 ) in Si very early in the development of the semiconductor physics [47], careful searches for EPR from holes bound to neutral acceptors (A 0 ) in Si were initially unsuccessful, as summarized by Kohn [48], who was also the first to point out that the problem likely resulted from the four-fold degeneracy of the A 0 ground state.…”
Section: Resultsmentioning
confidence: 99%
“…Random internal strains originating from crystal defects will thus lead to distributions of the separations of these TLS. The dependence of the width and form of such distributions on the concentration of point defects has been investigated previously [1] at temperatures above 1 K. Relaxation times T 1 and T 2 have been obtained in this temperature range from relaxation attenuation, saturation, and hole burning [2].…”
Section: Introductionmentioning
confidence: 98%